Forced Relocation after the indian ocean tsunami 2004 case study of vulnerable population in three relocation setlements in Galle,Sri Lanka - Fernando, Nishara (My University, 2010)
This study focuses on the impact of forced relocation on the livelihoods of residents who lived in the city of Galle, Southern Province of Sri Lanka, prior to the 2004 tsunami, who were later forcibly relocated into new settlements situated far from the city of Galle as a result of the "buffer zone regulation" (no construction zone). It further examines various livelihood strategies (i.e. coping and enhancement) employed against stresses and risks (i.e. income, housing, common infrastructure and fragmented relationship with the host community) emanating from forced relocation. Finally, it attempts to show how all these stresses and risks have added to increased social vulnerability, threatening the livelihood security of the relocated sample households in three research locations by adopting a socio-geographic approach. The empirical study is embedded in two main research areas: displacement and relocation research, and vulnerability and livelihoods research. Two conceptual frameworks of forced relocation (Thayer Scudder's Stress and Settlement Process, and Michael Cernea's Impoverishment Risks and Reconstruction Model for Resettling Displaced People) and another two conceptual frameworks of social vulnerability (Bohle's conceptual model on Double Structure of Vulnerability and the Sustainable Livelihoods Framework) were used to construct an analytical framework for the empirical study. Data was collected in three stages between September 2006 and March 2008 in three large resettlements 8-12 km away from the city of Galle using several data collection methods, namely detailed household questionnaires, in-depth interview schedules, key informant interviews, simple observations and PRA methods. Triangulation of methods was used with the purpose of improving the quality of data as well as to acquire a more holistic picture of the relocation process. Both qualitative and quantitative data analysis techniques were employed to analyse the collected data. As the study shows, firstly the tsunami and secondly the forced relocation into settlements far from the city were severe shocks to the studied households. As a result of these shocks, they had to begin their life from scratch. None of the interviewed householders wanted to move out of the city due to perceiving the negative consequences on their livelihoods, access to schools and other services. Unavailability of unused state owned land in the city forced government authorities to relocate most of the tsunami displaced people into iii settlements far from the city despite previous pledges made by the government to relocate them within Galle city. This has increased the uncertainty of relocatees about their future. Displaced people, however opposed to this move, did not have any permanent place to live other than the new settlements far from the city and in addition were unable to successfully cope with various issues and problems (limited space, lack of water, no electricity, poor construction of wooden houses etc) in their transitory shelters. Empirical data also pointed out increased income related stress owing to new household expenses (i.e. new transport cost, water bills and electricity bills) and disruption of income earning activities mainly due to transportation difficulties into the city and lack of income earning opportunities in the new area. This situation forced them to employ various livelihood strategies such as entering more household members into the workforce, starting new home based income earning activity and change of main income earning activity. Nevertheless, household surveys and in-depth interviews with selected household members proved that economically poor resettled households were unable to successfully cope with income related stresses. Additionally, other stress and risk factors such as poor housing quality, lack of common infrastructure, fragmented social relationships with the host community that extended up to physical violence caused some resettlers to move back to the buffer zone illegally or places close to the city by renting, selling or closing their new houses. Though there was a general institutional arrangement for relief and reconstruction soon after the tsunami, the study also shows that government officials at various levels were lacking relevant knowledge and capacities to handle the massive relocation process effectively. In this context, relocatees got increasingly frustrated as there was no solid external support system to successfully address their grievances and feeling of being neglected by relevant authorities, which is a major sign of social marginalization. This clearly indicates a sign of failure of tsunami induced forced relocation program in the Akmeemana Divisional Secretary Division in Galle district.